Developing cross-cultural awareness through foreign immersion programs: Implications of university study abroad research for global competency development. Issue 3 (4th April 2016) - Lokkesmoe, Karen J; Kuchinke, K. Peter; Ardichvili, Alexandre
Abstract : Purpose: – The purpose of this paper is to investigate the efficacy of foreign immersion programs in terms of increasing cross-cultural awareness among university students in business, accounting, human resources and agriculture. The authors extrapolate from their population to the practice of developing business professionals on international assignments. Design/methodology/approach: – This paper presents findings of a four-year, government-sponsored university exchange program involving 40 professional management and agriculture science students from four US and Brazilian top research universities who participated in a semester-long study abroad experience. Pre-departure and post-exchange data were collected using the well-established Intercultural Development Inventory (IDI). In addition, the authors collected academic performance data and verbal mid- and end-project personal assessments. Two of the authors of this paper served as project directors, the third as evaluation specialist. Findings: – Despite intensive pre-departure preparation, in-country support and cultural immersion, the research subjects failed to attain significant and consistently higher levels of intercultural awareness. Students tended to overestimate their own level of cross-cultural competence both before and after the program. While students tended to perform well academically and voiced high levels of satisfaction with their own overseas stay, objective measures of cross-cultural awareness did not mirror these outcomes. Research limitations/implications: – Multiple measures of cross-cultural competence exist, and it is possible that the development in areas other than those measured by the IDI did take place. It is also sensible to assume that cognitive development might take longer and was not captured by the post-test right after return. Practical implications: – The paper suggests that cross-cultural development requires carefully designed interventions, feedback and mentoring/coaching. Simply sending individuals on overseas assignments, no matter how well prepared and supported by the institution, does not guarantee the development of multi-cultural attitudes and cognitive frames of mind. Social Implications: – The development of cross-cultural competence has been described as a central concern for universities and workplaces alike. The burgeoning research literature on cross-cultural development reflects not only the importance of the topic but also the struggle to find effective pedagogical and andragogical approaches to fostering such development in university students, expatriate managers, working professionals and members of the workforce in general. Originality/value: – The paper presents evaluation findings of a carefully designed and well-supported exchange program over a period of four years and involving three cohorts of students. These students are at the cusp of moving into the workplace, where many will assume professional and leadership positions in international settings. Given the high failure rate of international development and placement and the increasing global interconnectedness of academic and business organizations, the paper suggests the need for carefully designed and well-supported overseas programs to maximize cross-cultural development.